On the Problem of Ethno-National Education of Artschool - Kamaeva, Marina Petrovna (Этническая культура, 2021)
The article is devoted to the study of the relevant issue in today’s world – the study of theoretical premises of modern concepts of ethno-national education. It examines the problems of educating the culture of interethnic relations in the youth environment. The relevance of the study is due to the need for the formation of attitudes towards interethnic tolerance among students, which determines the goal of the educational activities of each educational institution. The purpose of the article is to consider the theoretical foundations of ethno-national education and the possibilities of their practical application in educational work with students of a higher educational institution. The work was carried out at the empirical level of the structure of sociological knowledge. Methods of observation, questioning, interviewing and generalization of pedagogical experience allowed the author to determine the direction of work in the field of ethnic education of students. Based on the research carried out, the author draws conclusions about the quality of work in the field of ethno-national education of students at the university and offers recommendations for its improvement. The study showed predominantly supra-ethnic self-awareness of young people. Another unusual result of the study is a small percentage of students who speak their native (non-Russian) language – only 20 percent of the respondents. It is proposed that the parameters set require the pursuance of bigger researches on a nationwide scale.